2000
DOI: 10.1364/ao.39.006279
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution scanning surface-plasmon microscopy

Abstract: Surface plasmons (SP's) are electromagnetic surface waves that propagate along the interface between conductors and dielectrics. The k vector of these waves is larger than the free-space wave vector. The importance of SP's lies in the fact that they are extremely sensitive to small changes in the dielectric properties of substances that are in contact with the conductors. This property means that SP's have many sensor applications; however, when they are used in microscopic applications the lateral resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 17 publications
1
43
0
Order By: Relevance
“…The interference term from a uniform sample, assuming a linearly polarised reference beam of uniform amplitude, and linearly polarised light incident in the back focal plane (bfp) is given by (Somekh et al, 2000b):…”
Section: Interferometric Microscopy Methods For Determination Of Locamentioning
confidence: 99%
“…The interference term from a uniform sample, assuming a linearly polarised reference beam of uniform amplitude, and linearly polarised light incident in the back focal plane (bfp) is given by (Somekh et al, 2000b):…”
Section: Interferometric Microscopy Methods For Determination Of Locamentioning
confidence: 99%
“…On the other hand, Zare et al has shown that when the wavelength of excitation light switches from 638 nm to 532 nm, the propagation length on gold-plated surface can be reduced from 8.3 µm to 0.5 µm (in air), without significantly compromising the refractive index sensitivity [128]. Finally, by focusing the laser beam to a narrow line and scanning the laser line across the surface, the lateral resolution can be greatly improved, though it decreases temporal resolution for time-course scanning due to the scanning process [145,146].…”
Section: Spatial Resolution and Image Reconstructionmentioning
confidence: 99%
“…Thanks to the development of SPR techniques, some novel SPR-based microscopies have been proposed, such as, SPR enhanced fluorescence microscopy [47,48], surface enhanced Raman microscopy [49], SPR enhanced second harmonic generation microscopy [17,18], surface plasmon enhanced two-photon florescence [50], SPR multi-photon microscopy [51], wide-field SPR microscopy [52], SPR scanning near-field optical microscopy [53,54], far-field optical microscope based on in-plane surface plasmon imaging [55,56], and scanning surface plasmon microscopy SSPM [27,57,58]. Some of these new generation microscopies not only inherit the high sensitivity and sometimes SPR to interface, but also have a higher resolution beyond the diffraction limit of excitation light.…”
Section: Surface Plasmon Microscopymentioning
confidence: 99%